Utilisation of Internet of Things to Design a Gas Detector Device for Monitoring Gas Leakages in Underground Mines - AGORO, Nuhu Ndaka; IDOWU, Kayode Augustine; ADEGBUYIRO , Adeola (ABUAD Journal of Engineering and Applied Sciences, 2024)
The primary goal of the research was to design, evaluate, and fabricate a gas detection device using the Internet of Things (IoT). This subject matter was appropriate as it addressed a fundamental and significant facet of contemporary living in the mine. The objectives of the project were to design a gas detector device using an Arduino microcontroller, construct a gas detector device that rings a buzzer and sends an alert to an Android device on detection of harmful gas in the mine, and implement a gas detector device using the internet of things. Background data on gas detection technologies, pertinent standards and guidelines, field research, and durability factors related to the mines were gathered in order to define a test method. Arduino Uno was used as the control unit with other necessary components. Upon completion of the project, the gas detector device using the Arduino Uno was tested and found to work optimally.